2020
DOI: 10.1088/1674-1137/44/8/083105
|View full text |Cite
|
Sign up to set email alerts
|

Tensor form factors of P→ P, S, V and A transitions within standard and covariant light-front approaches *

Abstract: We investigate the tensor form factors of , and A transitions within the standard light-front (SLF) and the covariant light-front (CLF) quark models (QMs). The self-consistency and Lorentz covariance of CLF QM are analyzed via these quantities, and the effects of zero-mode are discussed. For the and A transitions, besides the inconsistency between the results extracted via … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…• Compared the numerical results of P → T transition with the ones of P → V transition obtained in our previous works [46,48] at q 2 = 0, it is found that: (i) For the c → q and b → q (q = u, d, s) induced transition with a light spectator quark, the former are smaller than the later, which is favored by the experimental data of radiative decays. For instance, our result T…”
Section: + 4bmentioning
confidence: 78%
See 2 more Smart Citations
“…• Compared the numerical results of P → T transition with the ones of P → V transition obtained in our previous works [46,48] at q 2 = 0, it is found that: (i) For the c → q and b → q (q = u, d, s) induced transition with a light spectator quark, the former are smaller than the later, which is favored by the experimental data of radiative decays. For instance, our result T…”
Section: + 4bmentioning
confidence: 78%
“…which suggested values given in the previous works [49], it covers properly the others values and therefore can reflect roughly the uncertainties induced by the model dependence of quark mass. Then, the parameters β listed in Table 6 [46], in which it have been assumed that β q q is same for V and T due to the lack of tensor meson decay constant data . In addition, the Appendix B: The CLF results for the tensor form factors of P → T transitions obtained in the previous paper…”
Section: Appendix A: Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…[84] by improving the correspondence between CLF and BS calculation, and has been tested in, for instance, Refs. [85][86][87][88][89][90][91][92][93]. Most of the results based on such improved self-consistent CLF approach for the decay constant and form factors generally agree with the experimental data and the predictions obtained by using Lattice QCD (LQCD) and light cone sum rules (LCSR) (some examples can be found in Refs.…”
Section: Numerical Results and Discussionmentioning
confidence: 59%
“…Perhaps, one of the most apt formulations for the analysis of exclusive processes involving hadrons may be provided in the framework of light-front (LF) quantization [38]. The semileptonic and rare D decays have also been analyzed by the light-front quark model (LFQM) [39][40][41][42][43][44][45][46][47] based on the LF quantization.…”
Section: Introductionmentioning
confidence: 99%